Illegal aliens and demons that must be exorcised from South Africa: Framing African migrants and xenophobia in post-apartheid narratives - Pineteh, Ernest A. (Cogent social sciences, 2017)
This article interprets narratives that have dominated the public sphere in post-apartheid South Africa, following the influx of African migrants. It uses qualitative data from personal interviews with local South Africans, excerpts from familiar political speeches and print media articles to tease out how the construction and intersection of public messages about foreigners and xenophobia have contributed to the recurrent attacks of African migrants. The article argues that although post-apartheid South Africa has become a prime migration destination, the country’s economic and psychosocial challenges have influenced the way citizens frame narratives about African migrants from other parts of the continent. These narratives are often fraught with images and metaphors that demonise and attempt to justify violence against African migrants. The article attempts to examine how the framing of such narratives provides a discursive space for understanding South Africans’ perceptions about African migrants and the multiple perspectives of xenophobia in post-apartheid South Africa.